2023
DOI: 10.1021/acs.jafc.3c00137
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophomins A–D Produced from Pseudomonas sp. HN8-3 Using an OSMAC Approach and Their Roles in Biocontrol of Phytophthora capsici in Cucumbers

Abstract: In this study, two new cyclic lipopeptides (CLPs) pseudophomins C (3) and D (4) and two known CLPs pseudophomins A (1) and B (2) were produced and characterized from the bacterial supernatant of Pseudomonas sp. HN8-3 by an OSMAC (one strain-many compounds) approach. OSMAC is a strategy that involves feeding of a single microorganism with divergent substrates to stimulate the production of new secondary metabolites. These pseudophomins were purified and identified via chromatographic methods, droplet collapse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…HN8−3, while pseudophomins A and B were coproduced in such PDB of this strain. 2 Intriguingly, L-Leu, L-norvaline and L-cyclopropylalanine as precursors were inactive for PDB of the NRPS coding for WLIP in this study. Additionally, L-Leu, L-Val, and L-Ile as precursors were also inactive (Ma Z, unpublished data) for PDB on the NRPS encoding for CLP bananamide from Pseudomons sp.…”
Section: ■ Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…HN8−3, while pseudophomins A and B were coproduced in such PDB of this strain. 2 Intriguingly, L-Leu, L-norvaline and L-cyclopropylalanine as precursors were inactive for PDB of the NRPS coding for WLIP in this study. Additionally, L-Leu, L-Val, and L-Ile as precursors were also inactive (Ma Z, unpublished data) for PDB on the NRPS encoding for CLP bananamide from Pseudomons sp.…”
Section: ■ Discussionmentioning
confidence: 50%
“…PDB for the Production of CLPs. Previous reports have shown that the amendment of protein amino acids L-Leu, 2 L-Ile, 27 and L-Val, 28 and nonprotein amino acids L-2-aminobytyric acid, 29 L-norvaline, 29 and L-cyclopropylalanine 29 in bacterial cultures will lead to the specific incorporation of these amino acids in the final CLPs; thus, this procedure will generate new CLP derivatives possessing of the diversification on peptidic sequences. Hence, we have first used protein amino acids L-Leu, L-Ile, and L-Val (Figure 2A) as precursors in PDB experiments for P. canadensis Q3−1.…”
Section: Bacterial Isolation and Identification And In Silicomentioning
confidence: 99%
See 3 more Smart Citations